Answer:
A. an = -3 + 4(n - 1)
Explanation:
The sequence given follows an arithmetic progression. This means the following term can be gotten by simply adding a factor to the previous term (or even the first term).
They are represented by the equation:
y(n) = a + r(n - 1)
Where y(n) is the nth term
a = first term
r = factor
Let us compare this with the sequence given:
The first term, a, is -3
We can get the factor, r, by using the second term, which is 1. This means n = 2.
=> 1 = -3 + r (2 - 1)
1 = -3 + r
=> r = 1 + 3 = 4
Therefore, putting a = -3 and r = 4, the sequence can be written as:
y(n) = -3 + 4(n - 1)